Instability of a spontaneously formed multiple-flux vortex in polariton condensates. (July 2015) - Chen, Ting-Wei; Cheng, Szu-Cheng; Hsieh, Wen-Feng
Abstract: A spontaneously formed vortex can occur in an incoherently pumped microcavity-polariton condensate which is a non-equilibrium system. The stability of this vortex depends on the flux quanta that the vortex owns. In this paper, we have investigated the dynamics of spontaneously formed vortices with multiple-flux quanta in incoherently pumped microcavity-polariton condensates. From the excitation spectra of a spontaneously formed vortex, we can study the stability of the vortex under different pump strength. The vortices with flux quanta less than four are dynamically stable within a wide range of pump strength. However, when the flux quanta of a vortex is greater than three and the pump power is above a critical pump strength, some imaginary parts of excitation modes of the vortex become positive. The vortex then becomes dynamically unstable and tends to split into several vortices with smaller flux quanta. Highlights: Without considering a potential trap or disorders, we study the dynamics of SFMVs in incoherently pumped MPCs through the complex Gross–Pitaevskii equation (cGPE) which is coupled to the reservoir polaritons. The size of SFMVs is inversely proportional to the square root of the pump power above the threshold. Moreover, the visibility of the vortex goes higher with respective to pump power increasing. The stability and collective-excitation spectra of a SFMV is investigated by applying the Bogoliubov excitation. When the pump power is low, we find that SFMVs subjected to excitations in an incoherently pumped MPC are surprisingly stable even without stirring, trapping or disorder potentials.